2019
DOI: 10.1002/cpt.1557
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide Association Study of Statin‐Induced Myopathy in Patients Recruited Using the UK Clinical Practice Research Datalink

Abstract: Statins can be associated with myopathy. We have undertaken a genomewide association study (GWAS) to discover and validate genetic risk factors for statin-induced myopathy in a "real-world" setting. One hundred thirtyfive patients with statin myopathy recruited via the UK Clinical Practice Research Datalink were genotyped using the Illumina OmniExpress Exome version 1.0 Bead Chip and compared with the Wellcome Trust Case-Control Consortium (n = 2,501). Nominally statistically significant single nucleotide poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 44 publications
1
28
0
Order By: Relevance
“…In patients on 40 mg SVT daily, the myopathy relative risk remained but was halved to~2.6 (95% CI 1.3-5.0) per C allele, in keeping with a dose-related ADR [86]. This association between SVT myopathy and rs4149056 has been replicated [89,174] and confirmed in recent large meta-analyses [110,116]. Furthermore, rs4149056 has also been linked to milder adverse outcomes encompassing myalgia, prescription reductions and/or minor biochemical (e.g., CK) elevations indicative of SVT intolerance [69,85,113,175].…”
Section: Slco1b1 Influx Transportermentioning
confidence: 71%
See 4 more Smart Citations
“…In patients on 40 mg SVT daily, the myopathy relative risk remained but was halved to~2.6 (95% CI 1.3-5.0) per C allele, in keeping with a dose-related ADR [86]. This association between SVT myopathy and rs4149056 has been replicated [89,174] and confirmed in recent large meta-analyses [110,116]. Furthermore, rs4149056 has also been linked to milder adverse outcomes encompassing myalgia, prescription reductions and/or minor biochemical (e.g., CK) elevations indicative of SVT intolerance [69,85,113,175].…”
Section: Slco1b1 Influx Transportermentioning
confidence: 71%
“…The GATM locus was associated with a reduced incidence of statin myopathy in two separate populations (combined SVT, ATV, PVT) with a meta-analysis OR for rs1719247 of 0.60 (95% CI 0.45-0.81, p = 6.0 × 10 −4 ) [126]. Several subsequent SRM studies of SRM have not replicated this finding [110,111,[240][241][242], although a recent candidate gene study of RVT myotoxicity in Han Chinese patients found a similar marginal protective effect of the GATM rs9806699 minor allele (p = 0.024) [109]. The lack of replication raises questions about the role of GATM in SRM; functional studies of GATM in human primary muscle cells may help resolve the discordant results.…”
Section: Glycine Amidinotransferase (Gatm)mentioning
confidence: 97%
See 3 more Smart Citations